The China shock, employment protection, and European jobs - Hedieh Aghelmaleki; Ronald Bachmann; Joel Stiebale (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
We investigate the effects of Chinese import competition on transitions into and out of employment using comparable worker-level data for 14 European countries. Our results indicate that, on average, Chinese imports are associated with an increased probability that employed workers become unemployed and with a reduction in worker flows from unemployment to employment. In countries with high levels of employment protection, incumbent workers are shielded against the risk of job loss due to Chinese competition, but unemployed workers' prospects seem to be particularly negatively affected in these countries. We also provide evidence that the effects of increased Chinese imports differ by worker groups and the tasks performed on the job.
Keywords: F14; F16; J23; J63; J64; 330; trade adjustments; China; import competition; worker flows; employment transitions; employment protection